PERSIAPAN PENDIDIKAN ANAK DIMULAI DARI MEMILIH JODOH - Hamid, Rusdiana (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2008)
The process to educate children is not easy. It should be well planned, well organized, focus and in line with Islamic thought. Preparation for children education should be started ever since a man or a woman tries to find his/her spouse. In Islam, the first fundamental requirement in choosing a soul mate is religion and good characters. A spouse who is devout to Allah the Almighty and his prophet Muhammad pbuh will generate a virtuous generation. Then, this generation is going to be the key people in creating peace and prosperiy on the earth.